Creativity and Technology: Unlimited Narrative Structures in the Transmedia World-Building - Gispert de Chia, Nuria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In the convergence of technology and narrative, transmedia worlds rise as limitless universes, offering audiences rich and multidimensional narrative experiences that transcend traditional platforms. This study provides an updated vision of these worlds, examining their complexity and construction methods, and offering a synthesis of digital narrative theories and practices. Furthermore, the study delves into the possibilities of transmedia universes and examines their adaptation and evolution in response to technological and cultural changes, revealing the synergy between creativity and technology that allows creators and audiences to co-create expansive narrative universes.